On the asymptotic expansion of the logarithm of Barnes triple gamma function - Koumandos, Stamatis; Pedersen, Henrik L. (MATHEMATICA SCANDINAVICA, 2009)
It is shown that the remainders in an asymptotic expansion of the logarithm of Barnes triple gamma function give rise to completely monotonic functions. Furthermore, error bounds are found.